THE CONCEPT OF GHOSРITАЛЬАЛЬ RÉDÉGICAL AND ITS ESSENCE - Isakulova N. J. (Journals Park Publishing, 2025)
This article presents the concept of geologic and its essence. It also identified the need to organize the educational process of students in hospitals and other health institutions, based on the interlinking of medicine and education. Similar and different features of therapeutic pedagogy, hospitable pedagogy, medical pedagogy, and inclusive pedagogy are highlighted.
Keywords: Therapeutic pedagogy, hospital pedagogy, medical pedagogy and inclusive pedagogy, medical and pedagogical integration, personal approach, health education, psychological help and support, social and cultural development, pedagogical analysis and monitoring.